2017
DOI: 10.1007/s12015-017-9782-9
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in the Regulation of Pluripotency and Reprogramming

Abstract: Pluripotent stem cells have great potential for developmental biology and regenerative medicine. Embryonic stem cells, which are obtained from blastocysts, and induced pluripotent stem cells, which are generated by the reprogramming of somatic cells, are two main types of pluripotent cells. It is important to understand the regulatory network that controls the pluripotency state and reprogramming process. Various types of noncoding RNAs (ncRNAs) have emerged as substantial components of regulatory networks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 161 publications
1
26
0
Order By: Relevance
“…Non-coding RNAs were demonstrated to be involved in the modulation of the expression of several genes, which suggested that they may influence the progression of tumors when they regulated tumorrelated genes. 23,24 LOXL1-AS1 was a newly discovered lncRNA first reported by Hauser et al 15 Subsequently, several studies reported its effects on prostate cancer and medulloblastoma. For example, Long et al 17 showed that LOXL1-AS1 expression was distinctly upregulated in prostate cancer and its knockdown suppressed tumor cell proliferation via regulating miR-541-3p and CCND1.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs were demonstrated to be involved in the modulation of the expression of several genes, which suggested that they may influence the progression of tumors when they regulated tumorrelated genes. 23,24 LOXL1-AS1 was a newly discovered lncRNA first reported by Hauser et al 15 Subsequently, several studies reported its effects on prostate cancer and medulloblastoma. For example, Long et al 17 showed that LOXL1-AS1 expression was distinctly upregulated in prostate cancer and its knockdown suppressed tumor cell proliferation via regulating miR-541-3p and CCND1.…”
Section: Discussionmentioning
confidence: 99%
“…Some well-researched lncRNAs, including HOTAIR, MALAT-1, HULC, and H19 have been proven to act as oncogenes or tumor suppressor genes and correlate with drug resistance [44][45][46][47]. LncRNAs regulate gene expression at the epigenetic, transcriptional, and posttranscriptional levels [32-34, 48, 49], and also regulate the reprogramming of induced pluripotent stem cells [50]. A few studies found that compared with healthy individuals, MALAT1 and MEG3 lncRNAs are overexpressed in patients with MM [51].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics of each patient were also established and recorded. Three patients were male, and the median age was 52 (48)(49)(50)(51)(52)(53)(54)(55)…”
Section: Patients and Cell Samplesmentioning
confidence: 99%
“…Noncoding RNAs are critical players in organizing the regulatory networks that establish or remove roadblocks in this reprogramming process 14–17 . Long non-coding RNAs (lncRNAs), which are >200 nucleotides in length and lack apparent open reading frames, may control gene activity at a transcriptional level via either cis or trans mechanisms 18 , 19 .…”
Section: Background and Summarymentioning
confidence: 99%